2020
DOI: 10.5334/tohm.526
|View full text |Cite
|
Sign up to set email alerts
|

Postural Directionality and Head Tremor in Cervical Dystonia

Abstract: Background: Although abnormal head and neck postures are defining features of cervical dystonia (CD), head tremor (HT) is also common. However, little is known about the relationship between abnormal postures and HT in CD. Methods: We analyzed clinical data and video recordings from 185 patients enrolled by the Dystonia Coalition. We calculated the likelihood of their HT and HT type ("regular" vs. "jerky") given directionality of abnormal head postures, disease duration, sex, and age. Results: Patients with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…With the exception of pitch (anterocollis vs. retrocollis), this directionality information is lost in clinical rating scales. Yet the directionality of pitch has been associated with likelihood of comorbid head tremor in CD 36 and in turn head tremor subtype is differentially associated with pain severity 37 . In our cohort, we found that there was no bias toward anterocollis versus retrocollis, left versus right in laterocollis (“tilt”, roll), and left versus right in torticollis (“rotation”, yaw).…”
Section: Discussionmentioning
confidence: 54%
“…With the exception of pitch (anterocollis vs. retrocollis), this directionality information is lost in clinical rating scales. Yet the directionality of pitch has been associated with likelihood of comorbid head tremor in CD 36 and in turn head tremor subtype is differentially associated with pain severity 37 . In our cohort, we found that there was no bias toward anterocollis versus retrocollis, left versus right in laterocollis (“tilt”, roll), and left versus right in torticollis (“rotation”, yaw).…”
Section: Discussionmentioning
confidence: 54%
“…This information could be used to determine whether the arms up maneuver and sensory tricks have differential effects on HT even for individual patients. Third, although in our cross-sectional design we found that the likelihood that raising arms decreases HT severity is independent of demographic variables, HT likelihood in CD is higher for older age at onset [ 13 14 ], longer disease duration [ 14 15 ], and female gender [ 1 14 ]. Longitudinal studies could determine whether individual patients exhibit changes over time in the relationship of HT to the arms up maneuver.…”
Section: Discussionmentioning
confidence: 92%
“…There has been great enthusiasm in recent years for developing more objective outcome measures that could be used to monitor abnormal movements for dystonia 20‐22,34‐37 . Presumably these measures would not be impacted by patient impressions, and they should be quite reliable.…”
Section: Discussionmentioning
confidence: 99%